2013
DOI: 10.1074/jbc.m112.347682
|View full text |Cite
|
Sign up to set email alerts
|

ras-induced Up-regulation of CTP:Phosphocholine Cytidylyltransferase α Contributes to Malignant Transformation of Intestinal Epithelial Cells

Abstract: Background: PC synthesis by the CDP-choline pathway is regulated by CCT␣. Results: Increased expression of nuclear CCT␣ in ras-transformed intestinal epithelial contributes to PC synthesis that is required for anchorage-independent growth. Conclusion: An expanded pool of nuclear CCT␣ is involved in malignant transformation by ras. Significance: CCT␣ is a potential target to restore anchorage-dependent growth sensitivity of cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
(66 reference statements)
0
19
0
Order By: Relevance
“…Ras-transformation likely regulates CCT at several different levels since ras-transformed fibroblasts had reduced CCT activity but increased CCTa mRNA and protein [155]. Arsenault et al [258] recently showed that CCT activity and PC synthesis rates were similar in control and oncogenic H-ras transformed intestinal epithelia cells (IEC) despite a 5-10-fold increase in CCTa mRNA and protein. The expression of CCTb mRNA and proteins was unaffected by H-ras.…”
Section: Ccta Involvement In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Ras-transformation likely regulates CCT at several different levels since ras-transformed fibroblasts had reduced CCT activity but increased CCTa mRNA and protein [155]. Arsenault et al [258] recently showed that CCT activity and PC synthesis rates were similar in control and oncogenic H-ras transformed intestinal epithelia cells (IEC) despite a 5-10-fold increase in CCTa mRNA and protein. The expression of CCTb mRNA and proteins was unaffected by H-ras.…”
Section: Ccta Involvement In Cancermentioning
confidence: 99%
“…Thus adhesion-independent growth of ras-transformed IEC, an indication of metastatic potential, is dependent on increased CCTa expression. While it is apparent that CCTa activity and PC synthesis was increased upon detachment of ras-transformed IEC [258], it is unclear if this alone was sufficient to promote cell survival.…”
Section: Ccta Involvement In Cancermentioning
confidence: 99%
“…However, a primary mechanism involving inhibition of CCT ␣ and/or CPT/CEPT is at odds with metabolic labeling studies that consistently show a reduction in choline incorporation into the substrates and products of these enzymes ( 21,28,30 ). To reconcile this discrepancy, we compared CCT ␣ , CK, and choline transport activities with the fl ux of radiolabeled choline through the CDP-choline pathway in apoptotic cells.…”
Section: Caspase Cleavage Of Recombinant Cct ␣mentioning
confidence: 97%
“…10A ), and mRNA expression profi les ( 50 ), we conclude that CTL1 is responsible for <70% of choline transport activity in MCF7 and MCF7-C3 cells and is inhibited by caspase 3-dependent and -independent processes. Based on metabolic labeling from other studies that show a general suppression of choline input in the CDP-choline pathway ( 21,27,30 ), we posit that inhibition of choline transport occurs in other apoptotic programs and, because of reduced input of choline into the pathway, secondary effects on CCT ␣ and/or CEPT/CPT have a lesser contribution to inhibition of PtdCho synthesis.…”
Section: Inhibition Of Choline Uptake In Camptothecin-treated Cellsmentioning
confidence: 98%
“…D609 was originally discovered as a potent inhibitor of phosphatidylcholine specific phospholipase C (PCPLC), which plays a major role in the survival and proliferation of cells [11-12]. An earlier study has shown that D609 is a powerful antioxidant which behaves like a glutathione mimetic drug [13].…”
Section: Introductionmentioning
confidence: 99%